Using cooperative learning during the COVID-19 pandemic: Evaluation and impact on Secondary Education - Sánchez Sánchez, Natalia; Roa González, Julián; Sánchez Sánchez, Almudena (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The Covid-19 pandemic has meant a remarkable change in the education system. The adaptations in the way of teaching have led to some methodologies taking precedence over others. Cooperative Learning requires interpersonal relationships and therefore it is expected that it has been affected by the pandemic. This article analyses 177 secondary classrooms and observes that CL is not sufficiently established but that its use is sensitive to the subject, the age of the teacher and the type of classroom.